(untitled) (Journal of Economic Additions, 2025)
This study aimed to identify the impact of electronic marketing on customer satisfaction from the perspective of a sample of clients at Echellalba Tour Travel and Tourism Agency in M’sila. To achieve the objectives of the study, the descriptive method was used, relying on an electronic questionnaire distributed to a sample of 110 clients of the agency under study, the data was analyzed using the JASP statistical software. One of the most important findings of the study is the existence of a statistically significant impact of electronic marketing on customer satisfaction at Echellalba Tour Travel and Tourism Agency in M’sila. Jel Classification Codes : M31, D12, L83.